Using Student Response Systems (Clickers) In The History Classroom - Britten, Thomas (Teaching History: A Journal of Methods, 2011)
Teaching United States history surveys as part of the core curriculum requires college level historians to ask themselves many questions. What information should we leave in or pull out? Should we emphasize content or process? How can we engage students in a subject that many regard as simply a "hoop" to jump through en route to graduation? One of the challenges for historians who take teaching responsibilities seriously is to create a stimulating learning environment that actively engages students and makes course material relevant. At the same time, of course, we need to deliver to students a meaningful introduction to the major themes and personalities in American history. We can measure success in accomplishing this feat by gauging the quantity and quality of student involvement in class. Class participation indicates that students are engaged, that they feel comfortable asking or answering questions, and that they care about what is occurring in the classroom. From the instructor's perspective, class participation provides critical feedback on student attention and comprehension and gives a strong indication of student investment in the learning process. But that raises another question: How can instructors objectively, fairly, and efficiently measure and assess participation, particularly in large classes with fifty or more students?